Chinese experts recommendation on the monitoring and management of variability in responsiveness to antiplatelet therapy. (21st March 2015) - ; Yong, Huo; Ya-Ling, Han; Run-Lin, Gao; Da-Yi, Hu; Yun, Zhang; Jun-Bo, Ge; Yong-Qiang, Zhao; Xu-Bo, Shi; Yi-Da, Tang; Zhen-Yu, Liu; et al.
Abstract: Antiplatelet agents are widely used in patients with coronary artery disease for the prevention of thrombotic events. However, individual responsiveness to antiplatelet agents is greatly varied, which is deemed as one of the most important risk factors for adverse clinic events, such as thrombosis and bleeding. Although studies on this aspect have lasted for more than a decade, the appropriateness of responsiveness variability monitoring and management for antiplatelet treatment remains controversial. Based on current clinical evidence, expert recommendations by a working group of Chinese Society of Cardiology of Chinese Medical Association were released focused on the methodology, clinical interpretation, and appropriateness of antiplatelet responsiveness variability monitoring and management.